Personality and teachers’ burnout stress: exploring the digital competence as personal job resource in allied health institutions - Hussain, Zawar; Chenmei, Cai; Saeed, Muhammad; Hassan, Nazia; Chiragh, Fiza (Frontiers in Psychology, 2024)
Introduction Job burnout has severe consequences for teachers and students. This study aimed to measure the direct effects of personality traits on job burnout-stress syndrome among allied health educators. Furthermore, teachers’ digital competence was evaluated as a personal job resource for mitigating the negative impact of burnout. Methods This study examined direct relationships between work-related stress syndrome and personality traits, namely, extroversion, agreeableness, conscientiousness, emotional stability, and openness to experience. Data was collected from 334 allied health institution teachers through a self-reported questionnaire. Linear regression analysis was used to test for direct effects. Moderating effects were evaluated using Andrew F Hays PROCESS macro v2.16.3. Results All five personality traits had a significant negative relationship to burnout and teachers’ digital competence moderated the relationship between personality traits and burnout. This study’s findings provide evidence, that personality is significantly related to job burnout among allied health educators. Conclusion These empirical findings conclude that personality traits are related to burnout in the non-Western culture of Pakistan. Furthermore, teachers’ digital competence acts as a personal job resource and potential moderator in the current digital working environment. Therefore, future teachers should enrich their digital competencies for improved performance, and advanced digital competency courses should be included in their curriculum.